Systematics of Pristimantis lacrimosus group (Anura, Strabomantidae) with the description of a new species from the eastern slopes of the Ecuadorian Andes. - Carrión Olmedo, Julio César (2020)
With 540 species, the neotropical genus Pristimantis is the most speciose vertebrate genus. As a result of its striking diversity, taxonomic reviews remain a challenge. Herein, we present an updated phylogeny of the Pristimantis lacrimosus group, report the presence of three unconfirmed candidate species, and describe a new species from Llanganates and Sangay National Parks. Our phylogeny includes for the first time samples of Pristimantis degener, P. eremitus, P. eugeniae, P. katoptroides and P. petersi. Based on our phylogeny, we add 6 species to the Pristimantis lacrimosus group. Through the integration of molecular, morphologic, and bioacoustic evidence, we describe a new species which was hidden under “Pristimantis petersi”. Pristimantis petersioides sp. nov. is most closely related to Pristimantis petersi and can be distinguished by its advertisement call, the presence of a discoidal fold and a snout rounded to truncate in dorsal view. Pristimantis petersi lacks discoidal fold and its dorsal snout shape is rounded. We suggest assigning the new species to the Endangered Red List category.